CAABL-AF (California Study of Ablation for Atrial Fibrillation): Mortality and Stroke, 2005 to 2013. (June 2018) - Srivatsa, Uma N.; Danielsen, Beate; Amsterdam, Ezra A.; Pezeshkian, Nayereh; Yang, Yingbo; Nordsieck, Eric; Fan, Dali; Chiamvimonvat, Nipavan; White, Richard H.
Abstract : Background: Ablation for atrial fibrillation (AF) is superior to medical therapy for rhythm control. We compared stroke and mortality among patients undergoing ablation for AF to matched controls in a large multiethnic population. Methods: Using discharge and surgical records from California nonfederal hospitals, we identified patients who had ablation and principal diagnosis of AF with at least 1 prior hospitalization for AF. We excluded cases with valve disease, open maze, other arrhythmias, or implantable devices. Matched controls were selected based on years of AF diagnosis, age, sex, and being alive the same number of days from the initial AF encounter to the ablation date. Clinical outcomes, including mortality, ischemic stroke, or hemorrhagic stroke, were assessed using a weighted proportional hazard model, adjusting for demographics, prior admissions with AF before the ablation, calendar year, and presence of chronic comorbidities. Results: There were 4169 ablation cases and 4169 weighted-matched controls; 39% percent of the ablation group was >65 years, 72% men, 84% white; mean follow-up was up to 3.6±0.9 years. In adjusted models, ablation was associated with significantly lower mortality (per patient-years) 0.9% versus 1.9%, hazard ratio=0.59 ( P <0.0001; confidence interval: 0.45–0.77); ischemic stroke (>30 days post-ablation ⩽5 years), 0.37% versus 0.59%, hazard ratio=0.68 ( P =0.04; confidence interval: 0.47–0.97); hemorrhagic stroke 0.11% versus 0.35%, hazard ratio=0.36 ( P =0.001; confidence interval: 0.20–0.64) compared with controls. Conclusions: In this large population-based study of hospitalized patients with nonvalvular AF, ablation was associated with lower mortality, ischemic stroke, and hemorrhagic stroke compared with controls.